The Role of Information Technology in Overcoming Business Development Barriers in the Era of Globalization - Sabrina Arsy; Ana Sakinah; Umi Makhbubi Zakiyah; Aini Zaqiyah; Nunuk Indarti (International Journal of Technology and Education Research, 2026)
Information Technology (IT) in overcoming business development barriers in the era of globalization. Globalization creates various obstacles such as increasingly fierce international competition, rapid market changes, limited access to information, and demands for operational efficiency. Through a literature review approach, this article identifies these key barriers and analyzes the contribution of IT as a strategic solution. IT plays a role in improving information access and expanding markets through digital platforms and modern marketing technologies. In addition, IT promotes operational efficiency through business process automation, system integration, and the use of management software. IT also supports data-driven decision making through big data analytics and business intelligence. However, IT implementation faces challenges such as high costs, limited human resource competencies, digital security risks, and resistance to change. Overall, IT is a key factor in strengthening business competitiveness in the global era, as long as companies are able to manage the challenges of its implementation.